Utilization of agricultural lignocellulosic wastes for biofuels and green diesel production. (March 2022) - Pocha, Chaitanya Kumar Reddy; Chia, Shir Reen; Chia, Wen Yi; Koyande, Apurav Krishna; Nomanbhay, Saifuddin; Chew, Kit Wayne
Abstract: The ever-growing human population has resulted in the expansion of agricultural activity; evident by the deforestation of rainfoamrests as a means of acquiring fertile land for crops. The crops and fruits produced by such means should be utilized completely; however, there are still losses and under-exploitation of these produces which has resulted in wastes being mounted in landfills. These underutilized agricultural wastes including vegetables and fruits can serve as a potential source for biofuels and green diesel. This paper discusses the main routes (e.g., biological and thermochemical) for producing biofuels such as bioethanol, biodiesel, biogas, bio-oil and green diesel from underutilized crops by emphasizing recent technological innovations for improving biofuels and green diesel yields. The future prospects of a successful production of biofuels and green diesel by this source are also explained. Underutilized lignocelluloses including fruits and vegetables serve as a prospective biofuel and green diesel generation source for the future prosperity of the biofuel industry. Graphical abstract: Image 1 Highlights: Underutilized fruits and vegetables as a source to produce biofuel and green diesel. Cost-efficient catalysts and process intensification improve biofuels yield. Continuous supply of waste materials is necessary for industrial scale plants. Conversion of fruits and vegetables to biofuels needs to be standardized.